Is a success story of an underdog more powerful than one of a similar other? examining effects of model similarity and success attribution on intention to exercise. Issue 2 (15th March 2022) - Quan, Lihong; Chung, Sungeun; Kim, Youllee; So, Jiyeon
ABSTRACT: Success stories are often used to promote health behaviors. This study examined how different features of others' success stories about achieving an exercise goal influence observers' intentions to exercise. The specific factors examined were success stories' model similarity (similar vs. underdog model) and success attribution type (internal vs. external attribution message) on individuals' expectations of their success and intentions to exercise. The results of an online experiment ( N  = 282) showed that success stories of similar models led to greater success expectancy than those of underdog models through the increased perception of model similarity. Further, success stories focusing on external – as opposed to internal – attribution resulted in greater success expectancy through increased external attribution of models' success. Success expectancy then increased intention to exercise. This study concludes by discussing the theoretical implications for social cognitive theory and attribution theory as well as practical implications for designing health promotion messages.